THE EFFECT OF SAQ (SPEED, AGILITY, AND QUICKNESS) TRAINING ON SOME PHYSICAL AND SKILL ABILITIES, AS WELL AS THE MAXIMUM ANAEROBIC CAPACITY OF FEMALE SOCCER PLAYERS (American Journal of Pedagogical and Educational Research, 2023)
The aim of the research is to prepare SAQ (Speed, Agility, and Quickness) training in developing some physical and skill abilities, as well as the maximum anaerobic capacity of female soccer players in North Oil Club in Kirkuk province (Iraq). The researcher used the experimental method to suit the nature of the research and identified the research population as women's clubs in Kirkuk, which are three clubs (North Gas, North Oil, and Al-Fattah) with a total of 80 players. The research sample was chosen by purposive sampling, and North Oil Club was chosen with 28 players, representing 35% of the research population. Eight players were selected for the exploratory experiments, and the research sample became 20 players divided into two groups: control and experimental, with each group consisting of 10 players. The researcher used statistical methods such as standard deviation, median, coefficient, Pearson’s R correlation coefficient, and paired samples t-test. The researcher concluded that SAQ training had a positive effect on developing physical and skill abilities, as well as the maximum anaerobic capacity for the experimental group, and that the high-intensity and repetitive interval training methods played a positive role in developing the physical and skill abilities, as well as the maximum anaerobic capacity for the experimental group. The researcher recommends the use of SAQ training in training units and the integration of physical abilities with basic skills in training units.